Protein SIC Secreted from Streptococcus pyogenes Forms Complexes with Extracellular Histones That Boost Cytokine Production - Westman, Johannes; Chakrakodi, Bhavya; Snäll, Johanna; Mörgelin, Matthias; Bruun Madsen, Martin; Hyldegaard, Ole; Neumann, Ariane; Frick, Inga-Maria; Norrby-Teglund, Anna; Björck, Lars; Herwald, Heiko (Frontiers in Immunology, 2018)
Innate immunity relies on an effective recognition of the pathogenic microorganism as well as on endogenous danger signals. While bacteria in concert with their secreted virulence factors can cause a number of inflammatory reactions, danger signals released at the site of infection may in addition determine the amplitude of such responses, and influence the outcome of the disease. Here we report that protein SIC, Streptococcal Inhibitor of Complement, an abundant secreted protein from Streptococcus pyogenes, binds to extracellular histones, a group of danger signals released during necrotizing tissue damage. This interaction leads to the formation of large aggregates in vitro. Extracellular histones and SIC are abundantly expressed and seen co-localized in biopsies from patients with necrotizing soft tissue infections caused by S. pyogenes. In addition, binding of SIC to histones neutralized their antimicrobial activity. Likewise, the ability of histones to induce hemolysis was inhibited in the presence of SIC. However, when added to whole blood, SIC was not able to block the pro-inflammatory effect of histones. Instead SIC boosted the histone-triggered release of a broad range of cytokines and chemokines, including IL-6, TNF-α, IL-8, IL-1β, IL-1ra, G-CSF and IFN-γ. These results demonstrate that the interaction between SIC and histones have multiple effects on the host response to S. pyogenes infection.